Efficiency of U.S. Dialysis Centers: An Updated Examination of Facility Characteristics That Influence Production of Dialysis Treatments. (18th November 2013) - Shreay, Sanatan; Ma, Martin; McCluskey, Jill; Mittelhammer, Ron C.; Gitlin, Matthew; Stephens, J. Mark
<x xml:space="preserve">Abstract</x> Objective To explore the relative efficiency of dialysis facilities in the United States and identify factors that are associated with efficiency in the production of dialysis treatments. Data Sources/Study Setting Medicare cost report data from 4, 343 free‐standing dialysis facilities in the United States that offered in‐center hemodialysis in 2010. Study Design A cross‐sectional, facility‐level retrospective database analysis, utilizing data envelopment analysis (DEA) to estimate facility efficiency. Data Collection/Extraction Methods Treatment data and cost and labor inputs of dialysis treatments were obtained from 2010 Medicare Renal Cost Reports. Demographic data were obtained from the 2010 U.S. Census. Principal Findings Only 26.6 percent of facilities were technically efficient. Neither the intensity of market competition nor the profit status of the facility had a significant effect on efficiency. Facilities that were members of large chains were less likely to be efficient. Cost and labor savings due to changes in drug protocols had little effect on overall dialysis center efficiency. Conclusions The majority of free‐standing dialysis facilities in the United States were functioning in a technically inefficient manner. As payment systems increasingly employ capitation and bundling provisions, these institutions will need to evaluate their efficiency to remain competitive.